PHYSICAL ENVIRONMENT, POPULATION PARAMETER, AND MORPHOMETRIC RECORDS MORPHOMETRIC OF THE MONITOR LIZARD IN PAPUA - Deny A. Iyai; Yubelince Y. Runtuboi (Fakultas Kehutanan UNIPA, 2019)
Many studies have explored animals without providing its physical environment, whereas, this information can provide broad understanding for the importance of ecological components. This study tried to combine some studies on how importance the ecological means on the density and population as well as morphometric of the monitor lizards. Data was analysed using SPSS version 18.0 and presented descriptively using tables and graphics. Results show that density and population had association with wide areas of islands and distances from mainland. Morphometric as well had association with carrying capacity and richness of feeding.